Analysis of Factors Affecting House Purchase Decisions at Bintang Residence in Medan City - Nainggolan, Fadila Rahma; Marpaung, Nicholas (Journal Arbitrase : Economy, Management and Accounting, 2023)
This study analyzes the factors that influence the decision of buying a home in Bintang Residence. Object of this study was all residents who have homes in in Bintang Residence. The purpose of this study is to investigate and analyze the influence of family, economic situation, lifestyle, perceptions, and the location of the home purchase decision on Housing in Bintang Residence. This type of research is quantitative descriptive study using survey method. The nature of this research is the study explained (explanatory). This study using simple random sampling method to retrieve data using a sample of 75 respondents to the Slovin formula. Data analysis uses Multiple Linear Regression with SPSS 16 program. The result of this research shows that the value of Adjusted R Square of 0.642. This shows the magnitude of the effect of independent variables (location, a reference group, economic circumstances, lifestyle, and perception) on the dependent variable (the home buying decision) was 64.2%. In other words 64.2% bound variables can be explained by the independent variable, while the remaining 35.8% is explained by other variables not included in the study. Simultaneous regression test results showed that simultaneous independent variable (X) consisting of location, a reference group, economic circumstances, lifestyle, and perceptions have a positive and significant impact on the variable (Y) is the decision of buying a home in in Bintang Residence. Pasial regression test results in a variable location, a reference group, economic circumstances, lifestyles and perceptions have a positive and significant impact on the home purchase decision on Housing in Bintang Residence. The dominant factor influencing the purchase decisions of Housing home in in Bintang Residence is the location factor.